MiR-15b-5p Regulates Collateral Artery Formation by Targeting AKT3 (Protein Kinase B-3). Issue 5 (May 2017) - Zhu, Ling-Ping; Zhou, Ji-Peng; Zhang, Jia-Xiong; Wang, Jun-Yao; Wang, Zhen-Yu; Pan, Miao; Li, Ling-Fang; Chen, Lin; Li, Chuan-Chang; Wang, Kang-Kai; Bai, Yong-Ping; Zhang, Guo-Gang
Abstract : Objective—: To identify circulating microRNAs that are differentially expressed in severe coronary heart disease with well or poorly developed collateral arteries and to investigate their mechanisms of action in vivo and in vitro. Approach and Results—: In our study, we identified a circulating microRNA, miR-15b-5p, with low expression that, nevertheless, characterized patients with sufficient coronary collateral artery function. Moreover, in murine hindlimb ischemia model, in situ hybridization identified that miR-15b-5p was specifically expressed in vascular endothelial cells of adductors in sham group and was remarkably downregulated after femoral artery ligation. Overexpressed miR-15b-5p significantly inhibited arteriogenesis and angiogenesis in mice. In vitro, both under basal and vascular endothelial growth factor stimulation, loss-of-function or gain-of-function studies suggested that miR-15b-5p significantly promoted or depressed the migration and proliferation of endothelial cells. We identified AKT3 (protein kinase B-3) as a direct target of miR-15b-5p. Interestingly, AKT3 deficiency by injection with Chol-AKT3-siRNA obviously suppressed arteriogenesis and the recovery of blood perfusion after femoral ligation in mice. Conclusions—: These results indicate that circulating miR-15b-5p is a suitable biomarker for discriminating between patients with well-developed or poorly developed collaterals. Moreover, miR-15b-5p is a key regulator of arteriogenesis and angiogenesis, which may represent a potential therapeutic target for ischemic disease. Abstract : Supplemental Digital Content is available in the text.